Clinical effects and gut microbiota changes of using probiotics, prebiotics or synbiotics in inflammatory bowel disease: a systematic review and meta-analysis - Zhang, Xiao-Feng; Guan, Xiao-Xian; Tang, Yu-Jun; Sun, Jin-Feng; Wang, Xiao-Kai; Wang, Wei-Dong; Fan, Jian-Ming (European journal of nutrition, 2021)
Purpose Probiotics have been reported to be beneficial for inflammatory bowel disease (IBD), but the types, number of strains, dosage, and intervention time of probiotics used remain controversial. Furthermore, the changes of gut microbiota in IBD’s patients are also intriguing. Thus, this meta-analysis was to explore the clinical effects and gut microbiota changes of using probiotics, prebiotics and synbiotics in IBD. Methods The search was performed in PubMed, Web of Science and the Cochrane library from inception to April 2020. Qualified randomized controlled trials were included. IBD’s remission rate, disease activity index and recurrence rate were extracted and analyzed. Changes in the gut microbiota of patients with IBD are comprehensively described. Results Thirty-eight articles were included. Probiotics, prebiotics and synbiotics can induce/maintain IBD’s remission and reduce ulcerative colitis (UC) disease activity index (RR = 1.13, 95% CI 1.02, 1.26, P < 0.05; SMD = 1.00, 95% CI 0.27, 1.73, P < 0.05). In subgroup analyses of IBD remission rate and UC disease activity index, we obtained some statistically significant results in some subgroup ( P < 0.05). To some extent, probiotic supplements can increase the number of beneficial bacteria (especially Bifidobacteria ) in the intestinal tract of patients with IBD. Conclusions Our results support the treatment of IBD (especially UC) with pro/pre/synbiotics, and synbiotics are more effective. Probiotic supplements that are based on Lactobacillus and Bifidobacterium or more than one strain are more likely to be beneficial for IBD remission. The dose of 10 10 –10 12 CFU/day may be a reference range for using probiotics to relieve IBD.